Earthquake design practice for buildings - Booth, E.D. (Edmund D.) (ICE Pub., 2014)
Earthquake Design Practice for Buildings, 3rd edition provides comprehensive, practical and easy to read advice for all engineers, designers and analysts of earthquake resistant structures. This new edition has been completely revised to account for the many developments that had taken place since the publication of the best-selling second edition. The third edition continues to provide comprehensive practical guidance and now covers: Threats to human activity from earthquakes and strategies employed to mitigate this Reference to SHARE, SESAME, synthetic ground motion derivation Major update of codes European and USA A new prestressed concrete Floor diaphragm design brought closer to US practice European ideas now incorporated New US and ISO material on contents Supplemental damping.